Isolation, Biochemical and Genomic Characterization of Glyphosate Tolerant Bacteria to Perform Microbe-Assisted Phytoremediation - Massot, Francisco; Gkorezis, Panagiotis; Van Hamme, Jonathan; Marino, Damian; Trifunovic, Bojana Spirovic; Vukovic, Gorica; d’Haen, Jan; Pintelon, Isabel; Giulietti, Ana María; Merini, Luciano; Vangronsveld, Jaco; Thijs, Sofie (Frontiers in Microbiology, 2021)
The increasing use of glyphosate in more intensive farming practices leads to growing ecotoxicological and human health concerns related to its presence and spread in the environment. Low-cost and in situ remediation applications such as microbe-assisted phytoremediation, arise as good options to remove, contain or degrade glyphosate from soils and waterbodies, and thus avoid its further spreading to non-target areas. In this work, we isolated bacteria from a chronically glyphosate exposed soil, evaluated their glyphosate minimum inhibitory concentration (MIC), in vitro degradation potential, in vitro plant growth-promotion traits, and whole genome sequencing of seven strains was performed. Two glyphosate tolerant strains, Ochrobactrum haematophilum P6BS-III and Rhizobium sp. P44RR-XXIV were further tested for their capacity to degrade glyphosate in a greenhouse microcosm assay using Lotus corniculatus L. Root colonisation was studied using Confocal Laser Scanning Fluorescence Microscopy (CLSM), and Scanning Electron Microscopy (SEM). Sixteen bacterial strains able to grow using glyphosate as the sole source of phosphorous were found. Several of these demonstrated a diverse spectrum of in vitro plant growth-promotion traits. A MIC test showed that strains can tolerate a wide range of glyphosate concentrations, ranging from 500 to 10,000 mg kg-1. The glyphosate degradation rate in batch cultures was 42 % for O. haematophilum P6BS-III, and 49% for Rhizobium sp. P44RR-XXIV. Microcosms assays indicated that the association of Lotus corniculatus with Ochrobactrum P6BS-III was the best combination yielding the highest glyphosate removal with an average of more than 97% of the total glyphosate removed after a 20-days growth period. Further efforts to evaluate the feasibility of this microbe-assisted phytoremediation pair at field scale will be performed.